Design of Virtual Reality Browser Platform for Programming of Quantum Computers via VR Headsets - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2020)
Quantum computers are expected to offer an effect similar to the influence of the early integrated circuit computers. According to current systems, it is predicted that they will play an effective role in the emergence of a stronger technology with an increasing speed. Some high-tech companies have quantum computer designs that they actively put into use from the research and development phase to the problem-solving phase and these computers use different architectures. Unlike the others, IBM launched a cloud-based software infrastructure in 2016 and first introduced its 5-qubit quantum computer, which consists of sequential quantum ports architecture, to the use of researchers and interested parties via its web servers. Programming is done by using quantum gates via a web interface called quantum composer. Significant progress has also been made in virtual reality technologies and virtual reality based browser platforms have been developed. In this paper, studies on the using and training of the IBM quantum composer platform through a browser designed on the basis of virtual reality are presented. © 2020 IEEE.
Keywords: cloud based software; quantum circuit; quantum composer; Quantum computer; virtual reality browsers